An Environmentally Friendly Method for N‐Methylation of 5‐Substituted 1H‐Tetrazoles with a Green Methylating Reagent: Dimethyl Carbonate. (26th September 2014) - Xie, Aming; Zhang, Qiang; Liu, Yangyang; Feng, Liandong; Hu, Xinyu; Dong, Wei
<x xml:space="preserve">Abstract</x> An environmentally friendly method was established for the N‐methylation of the 5‐substituted 1H‐tetrazoles with a green reagent: DMC. DABCO was the optimal catalyst, and hazardous chemicals were avoided in this protocol. A plausible catalytic mechanism is proposed, which consists of a DABCO‐activated process and a thermally induced rearrangement of tetrazole carbamates.